The Low Connection Between Informal Digital Learning of English and Willingness to Communicate: Investigating the “Scrolling Phenomenon” and Speaking Challenges among EFL Vocational Students - Nurhandayani Supraptiningsih; Ilham Sakti Aji (UIN Salatiga, 2026)
Informal Digital Learning of English (IDLE) provides extensive authentic input; however, its casual digital register often diverges from the formal sociopragmatic requirements of vocational contexts. This study investigates the impact of such informal exposure on Willingness to Communicate (WTC) among 229 vocational school students. To address self-report bias, the data were collected using a situated measurement protocol through a validated 15-item questionnaire that measured Receptive IDLE (consuming content), Productive IDLE (creating content), and WTC, following industry-specific simulations that anchored WTC in a professional rather than social context. Descriptive analysis revealed a